أسلوب الشرط فى صحيحي البخارى ومسلم : دراسة وصفية تحليلية - ياسر بن اسماعيل (International Islamic University Malaysia, 2006)
The study examines conditional styles in the books of Şahih al-Bukhari and Şahih Muslim, most especially the conditional sentences which utilize the conditional particles determined by the grammarian. The study aims at describing these sentences and analyzing their linguistic characteristics by retrieving all the samples which contain conditional particles in both books. Subsequently, both the protasis and the apodosis together with their conjunctions were determined. In describing the forms of conditional sentences in the two books, the study made use of the opinions of the grammarian and their accounts which has indirectly influenced determining common characteristics of conditional sentences in the two books on the one hand and the rules laid down by the grammarians, on the other. The study also analyses different linguistic aspects of conditional sentences namely the syntactical and semantic aspects such as sentences that were preceded by particles of oath or any other particles. The study also points out elision and extension of these sentences. The syntactical functions of the conditional sentences were also addressed as well as the nature of changes in those sentences. The samples analyzed in this study were taken primarily form the sayings of the Prophet himself and any sayings other than his which belonged to his companions or to those who came after them in those traditions were not included in the analysis.